Facile synthesis and bridgehead-functionalization of bicyclo[3.3.3]pentasiloxanes. Issue 3 (12th December 2017) - Yokouchi, Yuki; Ishida, Shintaro; Onodera, Tsunenobu; Oikawa, Hidetoshi; Iwamoto, Takeaki
Abstract : Various bicyclo[3.3.3]pentasiloxanes (BPSO) were successfully synthesized via regioselective functionalization at the bridgehead positions. Abstract : A fascinating but still rare bicyclic siloxane, bicyclo[3.3.3]pentasiloxane, was synthesized by the oxidation of a bicyclic silicon cluster and characterized using a combination of NMR spectroscopy and X-ray diffraction analysis. The bridgehead OSiMe3 groups of the siloxane were selectively and efficiently converted to O − K + (siloxide) by treating with t BuOK in the presence of 18-crown-6-ether. The resulting siloxides provided various bridgehead-functionalized bicyclo[3.3.3]pentasiloxanes after treatment with electrophiles.